Understanding Of Hadiths Based On The Concept Of Wasatiyyah Al-qaradhawi To Deal With Understanding Of Extremism - Muhammad Arif Yahya; Muhammad Razak Idris; Amran Abdul Halim; Muhammad Ikram Bin Abu Hassan; Mohamad Zulkifli Abdul Ghani (Center for Promoting Ideas, USA, 2024)
Indexed by ERA